Unveiling the therapeutic potential of ketamine in depression: A bibliometric analysis and research landscape overview - Norsuhana Omar, Zahiruddin Othman, Ahmad Shahril Abdul Halim, Rozaziana Ahmad, Md Rizman Md Lazin Md Lazim, Nazlahshaniza Shafin, Asma Hayati Ahmad, Rahimah Zakaria (Journal of Applied Pharmaceutical Science, 2024)
Ketamine has emerged as an effective option for treatment-resistant depression (TRD), with a quick and long-lasting antidepressant effect, as well as anti-suicidal benefits. This bibliometric analysis uses a quantitative approach to determine the trend in publication and research themes related to ketamine and depression research. The literature search was conducted using a specific search query from the Scopus database. The downloaded data were analyzed using Publish or Perish and VOSviewer tools to perform citation and keyword analyses, respectively. A total of 994 articles were analyzed. Studies on ketamine and depression have shown an increasing trend annually since 2012. While the journal of affective disorders published more ketamine and depression-related articles, higher impact studies published in the biology of psychiatry garnered the most citations. Ketamine and depression-related terms topped the keyword co-occurrence analysis. All keywords were grouped into four clusters, cognitive effects of ketamine, mechanisms underlying antidepressant effects of ketamine, its safety and tolerability, and its anti-suicidal effects in TRD. The identified research themes from this review serve as a guide for researchers, practitioners, policymakers, and funding agencies to understand the research landscape and identify areas where more research is needed.
Keywords: Ketamine, depression, bibliometric analysis, Harzing’s Publish or Perish, VOSviewer